COLLABORATIVE GOVERNANCE IN STRENGTHENING SOCIAL COHESION: A CASE STUDY OF THE DEVELOPMENT OF BHINNEKA PARK AS AN INCLUSIVE PUBLIC SPACE IN SURABAYA CITY - Alifatul Reniwati Zumroh; Ryco Tarnuwardhana Putra; Ika Devy Pramudiana (International Journal of Multidisciplinary Reseach, 2026)
This study explores the dynamics of Collaborative Governance in strengthening social cohesion through the development of Bhinneka Park as an inclusive public space in Surabaya. Rapid urbanization in major Indonesian cities often leads to social fragmentation and the fading of interactions among heterogeneous residents. Addressing these modern urban challenges requires a shift from rigid top-down approaches to a collaborative paradigm involving the government, private sector, and civil society. This research utilizes a qualitative descriptive case study method, positioning the researcher as the key instrument to examine the depth of collaborative dynamics. Data collection was conducted through triangulation, including in-depth interviews with government officials, CSR representatives, academics, and marginalized groups, alongside participant observation and documentation. The findings indicate that the development of Bhinneka Park represents a significant paradigm shift toward a multi-stakeholder ecosystem where the Surabaya City Government acts as a facilitative leader. By integrating private sector capital through transparent Corporate Social Responsibility (CSR) schemes and involving local communities in the planning phase, the project has successfully built trust and shared understanding. Conceptually, the park serves as a "third space" that manifests spatial justice, particularly by providing standardized accessibility for people with disabilities, thus shifting their status from mere observers to invited subjects. Sociologically, Bhinneka Park functions as an organic peace laboratory that deconstructs identity stereotypes and reduces social prejudice through cross-identity interactions. This process strengthens bridging social capital, where residents from diverse ethnic, religious, and economic backgrounds feel a sense of belonging and equal rights to the city. The integration of participatory governance and non-discriminatory design effectively mitigates horizontal conflicts and urban fragmentation. Ultimately, the study concludes that resilient social cohesion can be achieved when public spaces are managed as inclusive ecosystems prioritizing dialogue, spatial justice, and cross-sector accountability. This collaborative model serves as a vital precedent for other cities in using public space development as a sustainable social integration strategy amidst modern polarization.